1995
DOI: 10.1063/1.359925
|View full text |Cite
|
Sign up to set email alerts
|

Visible light emission from thin films containing Si, O, N, and H

Abstract: We report the fabrication, chemical, optical, and photoluminescence characterization of amorphous silicon-rich oxynitride (SiOZNY :H) thin films by plasma-enhanced chemical-vapor deposition. The film compositions were followed by changes in the refractive index. X-ray photoelectron and Fourier transform infrared spectroscopy indicate that the chemical composition is dominated by silicon suboxide bonding with N present as a significant impurity. A broad tunable photoluminescence (PL) emission is visible at room… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
62
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 45 publications
11
62
2
Order By: Relevance
“…Although the XPS study from Augustine et al 15 indicated that the phase separation of SiO x does not occur even after annealing at 1050°C for 30 min, it is generally agreed that the phase separation starts at a temperature of 400-700°C. Furthermore, obvious phase separation and formation of c-Si NCs have been observed by Fourier-transform infrared spectroscopy and TEM at a temperature of 900-1000°C.…”
Section: A Surface Compositionmentioning
confidence: 99%
“…Although the XPS study from Augustine et al 15 indicated that the phase separation of SiO x does not occur even after annealing at 1050°C for 30 min, it is generally agreed that the phase separation starts at a temperature of 400-700°C. Furthermore, obvious phase separation and formation of c-Si NCs have been observed by Fourier-transform infrared spectroscopy and TEM at a temperature of 900-1000°C.…”
Section: A Surface Compositionmentioning
confidence: 99%
“…12 However, the material produced was not silicon rich, and the authors ascribed the luminescence solely to defects. Their luminescence spectra exhibit a peak around 2.3 eV which shows no annealing-related redshift, and there is no evidence of silicon clusters from either x-ray photoelectron spectroscopy ͑XPS͒ or x-ray diffraction studies.…”
Section: ͓S0003-6951͑98͒03330-0͔mentioning
confidence: 99%
“…Some groups have reported bright, broadband emission from asgrown thin films of silicon-rich silica, 17 while other groups see nothing until their samples are annealed. 27 While some reports show a redshift of peak luminescence wavelength with increasing annealing temperature, 13,24,27 others exhibit a fixed spectral distribution. 14,28 Similarly, it is not clear whether temperature quenching of luminescence is significant in this material: some groups show a strong dependence of luminescence intensity on sample temperature, 28 others see no change on cooling samples to 70 K. 24 As yet there is no model which adequately explains the wide range of experimental observations: it seems possible that more than one mechanism contributes to luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] However, there is considerable uncertainty about the nature of the luminescence mechanism from silicon-rich silica. A number of possibilities present themselves: radiative recombination of confined excitons within silicon clusters ͑''quantum dots''͒, 23 defect luminescence, 24 interfacial effects at cluster surfaces, 25 and luminescence from novel siloxene molecules. 26 Each of these proposed mechanisms has its proponents and supporting experimental evidence, leading to a very confused picture.…”
Section: Introductionmentioning
confidence: 99%